Induction treatment with FOLFIRINOX or oxaliplatin-based doublet followed by long-course chemoradiotherapy and surgery in locally advanced rectal cancer. A systematic review and pooled analysis from phase II and III trials - Moretto, Roberto; Vetere, Guglielmo; Carullo, Martina; Ciracì, Paolo; Masi, Gianluca; Cremolini, Chiara (Cancer treatment reviews, 2024)
•Induction chemotherapy with FOLFIRINOX followed by long-course CTRT versus CTRT alone improved survival outcomes.•The lack of head-to-head comparisons among triplet and doublet induction in LARC represents an unmet need.•We conducted a systematic review and IPSD pooled analysis including phase II-III trials comparing triplet and doublet induction.•Induction with FOLFIRINOX was associated with improved survival outcomes and pCR rates compared to CAPOX.•FOLFIRINOX showed higher rates of G3-4 neutropenia and nausea/vomiting respect to CAPOX. The PRODIGE-23 study showed a higher benefit for FOLFIRINOX (5-fluorouracil, irinotecan and oxaliplatin) as induction chemotherapy followed by long-course chemoradiotherapy (CTRT) respect to neoadjuvant CTRT alone both followed by total mesorectal excision (TME) in terms of disease-free survival (DFS) and overall survival (OS) in locally advanced rectal cancer (LARC). The added value of treatment intensification with irinotecan, over the doublet induction with fluoropyrimidine and oxaliplatin is still debated. To assess survival, pathological complete response (pCR) rate, and safety from phase II-III trials comparing triplet and doublet induction both followed by CTRT and TME in LARC. After a systematic literature review of PubMed, Embase, Cochrane, American Society of Clinical Oncology and European Society for Medical Oncology meetings’ libraries, data from Kaplan-Meier (KM) curves were extracted from phase II-III clinical trials. Phase II-III trials including at least one treatment arm with doublet or triplet induction chemotherapy without biological agents administered for a minimum of 3 months followed by long-course CTRT and TME and with at least 48 months of follow-up were selected. When available, the neoadjuvant CTRT alone arms of the selected studies were included as a comparator reference treatment. Individual patient DFS and OS data were extracted from Kaplan-Meier plots of original trials through graphical reconstruction between April 10th and May 19th, 2024. A pooled analysis was conducted, and results were validated in a subsequent network meta-analysis (NMA). pCR rates and grade ≥ 3 adverse events rates were also collected. Primary endpoints were DFS and OS between triplet and doublet induction. Secondary endpoints were DFS and OS between neoadjuvant CTRT alone and triplet or doublet induction as well as pCR rates and safety profile among different arms. Out of 674 patients enrolled in 3 trials, 231, 161 and 282 were treated with FOLFIRINOX or CAPOX (capecitabine and oxaliplatin) followed by CTRT or neoadjuvant CTRT alone, respectively. 5-year DFS rates were 73.1 % [95 %CI: 67.2 % – 79.0 %], 61.7 % [95 %CI: 53.9 % – 69.5 %] and 65.1 % [95 %CI: 59.4 % – 70.8 %] for triplet induction, doublet induction, and neoadjuvant CTRT alone, respectively. 5-year OS rates were 86.8 % [95 %CI: 82.3 % – 91.3 %], 74.7 % [95 %CI: 67.6 % – 81.8 %], and 79.6 % [95 %CI: 74.9 % – 84.3 %] for FOLFIRINOX, CAPOX, and neoadjuvant CTRT alone, respectively. Triplet induction showed longer DFS and OS respect to doublet induction (HR for DFS: 0.67 [95 % CI 0.47 – 0.96], p = 0.03; HR for OS: 0.49 [95 % CI 0.31 – 0.78], p = 0.003) with a trend for superiority when compared with neoadjuvant CTRT alone (HR for DFS: 0.77 [95 % CI 0.57 – 1.05], p = 0.10; HR for OS: 0.67 [95 % CI 0.45 – 1.01], p = 0.06). No difference was observed between the doublet induction and neoadjuvant CTRT groups. pCR rates were higher for patients treated with FOLFIRINOX (27.7 %) respect to subjects receiving CAPOX (19.7 %, p = 0.02) or neoadjuvant CTRT alone (12.5 %, p < 0.0001). Triplet was associated with higher rates of severe neutropenia (17 % vs 1 %, p < 0.0001) and nausea-vomiting (11 % vs 3 %, p = 0.02) respect to doublet induction. Induction with FOLFIRINOX showed better survival outcomes and pCR rates respect to CAPOX at the price of increased G3-4 neutropenia and nausea/vomiting. A randomized study comparing triplet and doublet chemotherapy in the frame of a total neoadjuvant treatment strategy is widely warranted.